Statistical analysis of the development of serfdom farms in the Vilnius and Dysna districts in the middle of the 19th century - Stasys Pamerneckis (Lietuvos Istorijos Studijos)
The decay of feudal relations and intensification of commodity production is analysed on the basis of compulsory inventories in the middle of the 19th century.